Projeto do sistema de elevação para uma bancada de transportadores de correia para manuseio de minério - CASTRO, Maycon Magalhães (2022)
The present work deals with the design of a system for lifting and tilting a belt conveyor in scale for the Fluid Dynamics and Particulate Laboratory (FluidPar) of the Tecnolágo Department, in partnership with the Federal University of Pará / Campus Tucuruí. From the methodological analysis with concepts of mechanical projects from different authors, as well as the analysis of the current situation of the laboratory and its benches, the possible solutions available in terms of lifting and handling systems that can meet the project in question are evaluated. Among the solutions evaluated, an ACME trapezoidal spindle lifting system was chosen as the solution with the greatest potential for success. The geometry of the project is established, the calculations of the required motor power are presented, as well as the possible requests on the spindle and the mechanical design of the solution is developed. Finally, the specifications of the components, the results and the final design of the bench are presented.